CRISPR/Cas9-mediated genomic insertion of functional genes into Lactiplantibacillus plantarum WCFS1 - Kamilla Wiull; Lisa K. Haugen; Vincent G. H. Eijsink; Geir Mathiesen (Microbiology Spectrum)
ABSTRACT Lactiplantibacillus plantarum, a natural inhabitant of the human body, is a promising candidate vehicle for vaccine delivery. An obstacle in developing bacterial delivery vehicles is generating a production strain that lacks antibiotic resistance genes and contains minimal foreign DNA. To deal with this obstacle, we have constructed a finetuned, inducible two-plasmid CRISPR/Cas9-system for chromosomal gene insertion in L. plantarum. The knock-in plasmid was designed with a cassette-like structure to simplify the insertion of target DNA and streamline the CRISPR/Cas9 genome editing, bringing it one step closer to becoming a routine procedure. We demonstrate that the system enables efficient insertion of expression cassettes for both inducible and constitutive production of a fluorescent reporter protein, mCherry, and for inducible production of the receptor-binding domain (RBD) of the SARS-CoV-2 virus. Two variants of RBD were successfully expressed, one directed to the cytoplasm and one directed to the cell surface. All the knock-in strains produced the target protein, although with lower yields than strains with plasmid-encoded expression.IMPORTANCEGenetic engineering of lactic acid bacteria, such as Lactiplantibacillus plantarum, has proven to be difficult. This study presents an inducible two-plasmid CRISPR/Cas9-system for inserting genes into the chromosome of Lactiplantibacillus plantarum. Our system successfully knock-in four expression cassettes varying in length from ~800–1,300 bp with high efficiency and insert an expression cassette encoding a SARS-CoV-2 antigen receptor-binding domain (RBD) with an anchor mediating surface display, which has not been achieved previously using CRISPR/Cas9. We demonstrate the production of the insertion genes. Importantly, the plasmid carrying the SgRNA, Cas9, and homology-directed repair template is designed for easy component exchange. These plasmids represent valuable contributions to the field as they could facilitate rapid CRISPR/Cas9 engineering of L. plantarum strains.